A Novel Internal Negative Pressure Delivery System in Prepectoral Breast Reconstruction—Preliminary Experience. Issue 1 (28th January 2022) - Paul, Robert
Abstract : Background: Seroma remains a common complication after breast surgery, despite meticulous surgical technique to obliterate dead space and use of standard postsurgical drains for fluid evacuation. Therefore, novel approaches are needed. The Interi System is an internal, negative-pressure delivery system consisting of a manifold that is a silicone tubing with a central trunk and three peel-apart channeled branches connected to an external therapy unit, which simultaneously delivers continuous negative pressure of 125 mm Hg and removes excess fluid from internal tissue planes. This retrospective study evaluated the safety and effectiveness of Interi compared with standard drains in consecutive patients undergoing immediate, prepectoral, acellular dermal matrix-assisted, and implant-based breast reconstruction. Methods: Patient records were reviewed, and data on demographics, mastectomy, and reconstructive variables, postoperative complications, fluid output volume, and manifold/drain duration were retrieved and compared between the two groups. Results: Interi was used in 23 patients (38 breasts) and standard drains in 23 patients (39 breasts). Patients in both groups were well matched in all demographic, reconstructive, and mastectomy variables. Interi duration was significantly shorter than drains (16.7 versus 19.7 days; P = 0.020). There were no instances of seroma formation after removal of the manifold, edematous flap, or reconstructive failure with Interi. Seroma rate was 20.5% after drain removal ( P = 0.005). All other complications were similar between the two groups. Conclusion: Interi effectively removed excess fluid from internal tissue compartments in prepectoral breast reconstruction and may offer significant improvement over current standards of care for seroma prevention in this procedure.